Plantability and corn productivity: influence of furrow opener mechanisms and oat straw management - Santos dos Santos, Luana; Modolo, Alcir José; da Rocha Campos, José Ricardo; da Silva Monteiro, Pedro Henrique; Sgarbossa, Maicon; Medeiros Gonçalves, Larisse (Revista Ceres, 2023)
Straw management associated with furrow opener mechanisms under a no-tillage system can enable better yields in the corn crop. Thus, this study aimed to evaluate corn productivity under a no-tillage system as a function of furrowing mechanisms and oat straw management. This research was conducted in the 2019/2020 growing season in Pato Branco, Paraná, Brazil, in a factorial scheme consisting of furrow opener mechanisms (shank and double disk) and oat straw management (rolled, desiccated, and crushed), with four replications. Oat dry matter, furrow depth, furrow width, tilled soil area, emergence rate index, initial and final plant stand, initial and final plant height, initial and final stem diameter, ear insertion height, number of rows per ear, number of grains per row, ear length, ear diameter, thousand-grain weight, and productivity were evaluated. The results were subjected to analysis of variance by the F-test at a significance 5% probability and the means were compared by Tukey’s test. Corn development, yield, and productivity were more influenced by the furrow opener mechanisms, standing out the use of a shank compared to the double disk.